THE IMAGE OF THE MOUNTAINBEG IN THE WORK OF THE NURALI KABUL - Qurbonova, Gulbahor (FILOLOGIYA UFQLARI JURNALI, 2024)
The article reflects on the velvety Colorite in the stories of the writer Nurali Qobul. The behavior of the velvet mountains, the animals in it, the mountain dogs with nature guards, was subject to analysis. It is illuminated that the mountainbegi, whose task is to preserve the mountain and its riches, harm nature, abuse their duties. It is revealed that the mountainbegis who caused harm to nature would eventually be punished by nature.